2018
DOI: 10.1007/s10549-018-4700-7
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity between MUC1 antigen and MCA: false elevation of serum CA 15-3 level in pregnant and lactating women by Ma695–Ma552-based assay

Abstract: The CA 15-3 assay using 115D8-DF3 antibody pair is more suitable for monitoring therapy in pregnancy-associated breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Liang et al [23] found that serum CA 15-3 levels detected by Ma695-Ma552-based assay was abnormally and significantly higher both in pregnant and in lactating women than in non-pregnant women. This study suggests caution when interpreting the results, taking into account what kind of laboratory assay was used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liang et al [23] found that serum CA 15-3 levels detected by Ma695-Ma552-based assay was abnormally and significantly higher both in pregnant and in lactating women than in non-pregnant women. This study suggests caution when interpreting the results, taking into account what kind of laboratory assay was used.…”
Section: Literature Reviewmentioning
confidence: 99%